MENINGKATKAN MINAT BERWIRAUSAHA PADA PEREMPUAN DI KOTA TASIKMALAYA - Nurlinawaty, Rina; Putri Lestari, Suci (JURNAL EKONOMI PERJUANGAN, 2024)
This research is based on the potential and opportunities that women can have for entrepreneurship which is useful for developing their business or even building a new business. The aim of this research is as an effort to determine the factors that influence women's interest in entrepreneurship in the city of Tasikmalaya. By conducting this research, it is hoped that we can find out the main factors that can arouse the interest of women in Tasikmalaya City to become entrepreneurs. This research was conducted on women who have not yet started a business or already have a business in the city of Tasikmalaya. survey methods and quantitative approaches, and sampling using sampling techniques. The data source used is primary data, and the data collection technique used is a questionnaire. Hypothesis testing in this research uses SEM-PLS analysis. From the research results, it is known that economic factors most encourage women to become entrepreneurs as a solution to meet their daily needs.